(untitled) (PJDOL, 2023)
AThis study evaluates comparative effectiveness of teaching modes i.e. video programmes, tutorial, textbook, and online web being used in Distance Education system of Chinese Open University, Beijing. Special emphasis has been given to video programmes. Population of the study was graduate students enrolled in different courses having online and video programmes along with tutorial and textbooks at the Beijing Study Centre of the University. A sample size of 300 including both male and female students was selected, and data were collected through a selfadministered questionnaire. Besides teaching modes, students’ demographics as well as the reasons for studying distance education were variables of the study. T